Information on the clinical progression of corridor disease in Bos indicus cattle naturally infected with buffalo-derived Theileria parva, to aid in early diagnosis of the disease - CGIAR Research Program on Livestock (2021)
This information will aid in early diagnosis of the disease based on clinical signs (important as laboratory diagnoses based on examination of blood samples are unreliable).